PRO AND CON FOR THE APPLICATION OF THE INFORMATION TECHNOLOGIES IN THE EDUCATION - Papanov, Stoyan Iliev; Petkova, Ekaterina Georgieva; Traikova, Nikoleta Ivanova (European Scientific Journal, ESJ, 2014)
The computer is a great student assistant in the process of digestion, understanding and remembering of new information. It helps finding the right means for individual work and control. Through the computer and the computer technologies a specific new studying environment is created. The electronic dialogue conducted with the computer creates new rules, norms, and educational technologies between the teacher and the student. Objective: The current paper represents analysis of students’ opinion (medical nurses) about the application of computer technologies in the process of learning in study course “Medical equipment in the nursing practice”.